Early Outcome, Cosmetic Result and Tolerability of an IOERT-Boost Prior to Adjuvant Whole-Breast Irradiation - Jazmati, Danny; Bölke, Edwin; Halfmann, Kati; Tamaskovics, Bálint; Ruckhäberle, Eugen; Fehm, Tanja; Hoffmann, Jürgen; Krug, David; Nestle Krämling, Carolin; Corradini, Stefanie; Budach, Wilfried; Mohrmann, Svjetlana; et al. (Cancers, 2022)
Background/Aims: Due to its favorable dose distribution and targeting of the region at highest risk of recurrence due to direct visualization of tumor bed, intraoperative electron radiation therapy (IOERT) is used as part of a breast-conserving treatment approach. The aim of this study was to analyze tumor control and survival, as well as the toxicity profile, and cosmetic outcomes in patients irradiated with an IOERT boost for breast cancer. Materials and Methods: 139 Patients treated at our institution between January 2010 and January 2015 with a single boost dose of 10 Gy to the tumor bed during breast-conserving surgery followed by whole-breast irradiation were retrospectively analyzed. Results: 139 patients were included in this analysis. The median age was 54 years (range 28–83 years). The preferred surgical strategy was segmental resection with sentinel lymphonodectomy (66.5%) or axillary dissection (23.1%). Regarding adjuvant radiotherapy, the vast majority received 5 × 1.8 Gy to 50.4 Gy. At a median follow-up of 33.6 months, recurrence-free and overall survival were 95.5% and 94.9%, respectively. No patient developed an in-field recurrence. Seven patients (5.0%) died during the follow-up period, including two patients due to disease recurrence (non-in-field). High-grade (CTCAE > 2) perioperative adverse events attributable to IOERT included wound healing disorder (N = 1) and hematoma (N = 1). High-grade late adverse events (LENT-SOMA grade III) were reported only in one patient with fat necrosis. Low-grade late adverse events (LENT-SOMA grade I-II) included pain (18.0%), edema (10.5%), fibrosis (21%), telangiectasia (4.5%) and pigmentation change (23.0%). The mean breast retraction assessment score was 1.66 (0–6). Both patients and specialists rated the cosmetic result “excellent/good” in 84.8% and 87.9%, respectively. Conclusion: Our study reports favorable data on the cosmetic outcome as well as the acute and early long-term tolerability for patients treated with an IOERT boost. Our oncologic control rates are comparable to the previous literature. However, prospective investigations on the role of IOERT in comparison to other boost procedures would be desirable.
CRIS-Team Scopus Importer:2025-10-13
Keywords: breast cancer; clinical outcome; LENT-SOMA; radiation therapy; skin reaction